2012
DOI: 10.1002/adfm.201102350
|View full text |Cite
|
Sign up to set email alerts
|

Functional Polysaccharide Composite Nanoparticles from Cellulose Acetate and Potential Applications

Abstract: An in situ technique for preparing composite nanoparticles from hydrophobic cellulose acetate and hydrophilic polysaccharides using nanoprecipitation is presented. This technique allows the nanoparticles' surface properties to be tuned very specifi cally. Spherical, narrow-size-distributed composite nanoparticles of different size, charge, functionality, and increased stability can be generated by using hydroxyethyl cellulose, carboxymethyl cellulose, low molecular weight chitosan, and amino cellulose. The inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 28 publications
0
41
0
Order By: Relevance
“…Wongsasulak et al (2010) have proposed the use of cellulose acetate and egg albumin as an edible nanofibrous thin films, which could aid new functionalities regarding the in vivo controlled release of pharmaceuticals and nutraceuticals in the gastrointestinal tract. Kulterer et al (2012) demonstrated an in situ nanoprecipitation technique for preparing composite NPs from cellulose acetate and hydrophilic polysaccharides including hydroxyethyl cellulose, carboxymethyl cellulose, low molecular weight chitosan and amino cellulose. The functional composite NPs exhibited great potential for the dispersion and delivery of hydrophobic substances in aqueous systems.…”
Section: Esterified Cellulose Containing Aliphatic Moietiesmentioning
confidence: 99%
“…Wongsasulak et al (2010) have proposed the use of cellulose acetate and egg albumin as an edible nanofibrous thin films, which could aid new functionalities regarding the in vivo controlled release of pharmaceuticals and nutraceuticals in the gastrointestinal tract. Kulterer et al (2012) demonstrated an in situ nanoprecipitation technique for preparing composite NPs from cellulose acetate and hydrophilic polysaccharides including hydroxyethyl cellulose, carboxymethyl cellulose, low molecular weight chitosan and amino cellulose. The functional composite NPs exhibited great potential for the dispersion and delivery of hydrophobic substances in aqueous systems.…”
Section: Esterified Cellulose Containing Aliphatic Moietiesmentioning
confidence: 99%
“…The same group recently reported an in-situ technique for the preparation of composite nanoparticles using nanoprecipitation from hydrophobic cellulose acetate with a number of hydrophilic polysaccharides (hydroxyethyl cellulose (HEC), carboxymethyl cellulose (CMC), low-molecular-weight chitosan (L-CHI), and amino cellulose (AC)) [63]. Kulterer et al [63] stated that the integration of different polysaccharides enabled the formation of composite nanoparticles with different sizes, charges, and effective Zeta-potentials, indicating that these hydrophilic polysaccharides bound to the CA nanoparticle matrix during the precipitation process and determined their surface characteristics.…”
Section: Cellulose Acetatementioning
confidence: 99%
“…Kulterer et al [63] stated that the integration of different polysaccharides enabled the formation of composite nanoparticles with different sizes, charges, and effective Zeta-potentials, indicating that these hydrophilic polysaccharides bound to the CA nanoparticle matrix during the precipitation process and determined their surface characteristics. The successful entrapment of pyrene (a hydrophobic fluorescent dye) into CA/CMC nanoparticles demonstrates great potential to be used in the pharmaceutical industry and bio-or food technology, as delivery of hydrophobic substances in aqueous media.…”
Section: Cellulose Acetatementioning
confidence: 99%
“…Polysaccharide-based composites have been the subject of numerous studies and have been proposed as favorable materials in a wide range of technological and bio-based applications (Ghorai et al 2013;Travan et al 2011;Pandey et al 2013;Kulterer et al 2012;Shingel and Marchessault 2006;Murugan and Ramakrishna 2004;Buchtová et al 2013;Stodolak et al 2009;Habibi and Dufresne 2008). Biocompatibility and biodegradability of starting materials, together with their large availability in nature, are added values for composites intended to perform medical and biobased functions.…”
Section: Introductionmentioning
confidence: 99%